A noise adaptive symbol timing synchronization algorithm for software radio receivers - O'MAHONY, DONAL EDWARD; NOLAN, KEITH EDWARD; DOYLE, LINDA (My University, 2004)
Software radio promises tremendous benefits from both commercial and military standpoints. Currently, there are a number of different 'shades' of software radio based on the use of FPGAs, DSP chips or general-purpose processors to perform the signal processing. There are also hybrids between these three platforms. The Network and Telecommunications Research Group (NTRG) approach is to focus on the use of a general-purpose processor (GPP). This maximizes the reconfigurability of the system. The use of a GPP to perform signal processing for communications applications presents the developer with challenges but it also presents some opportunities. We argue new classes of algorithms are required which will exploit the advantages and negate the disadvantages of using a GPP. Indeed other researchers have already started this programme of 'algorithmic advances'. This paper discusses the issues involved and reviews some existing developments. We present our own progress in developing a noise adaptive symbol synchroniser.
Proceedings of MILCOM 2004 Military Communications Conference
PUBLISHED
Monterey, Cailfornia
Keywords: Electronic & Electrical Engineering